A density functional theory study on the superacidity of sulfuric, fluorosulfuric, and triflic acid derivatives with two cyclopentadiene rings: ion pairs formation in the gas phase†. (23rd June 2019) - Valadbeigi, Younes; Vianello, Robert
Abstract: The gas phase acidity of organosulfuric acid derivatives with two cyclopentadiene rings replacing the doubly‐bonded oxygen atoms was computationally assessed using the B3LYP DFT functional and 6–311++G(d, p) basis set. Introduced five‐membered rings increased the acidity through the delocalization of the excess negative charge in conjugates bases and by providing positions to accommodate electron withdrawing substituents such as F and CN. The calculated enthalpies of deprotonation (∆ H acid ) of polycyanated systems were as low as 227.8 to 263.2 kcal mol –1 indicating exceptional superacidity. Substitution of one OH moiety by F or CF3 groups offered additional acidifying effect by preventing prototropic tautomerism in the neutral acids that acts towards lowering the acidity. The designed systems spontaneously protonated H2 O and NH3 in the gas phase and produced stable ion pair clusters. Abstract : The gas phase acidity of organosulfuric acid derivatives with two cyclopentadiene rings replacing the doubly bonded oxygen atoms was computationally assessed and many new highly acidic systems were identified with deprotonation enthalpies as low as 227.8 to 263.2 kcal mol –1 . Substitution of the OH moiety by F or CF3 groups offered additional acidifying effect by preventing prototropic tautomerism in neutral acids. The designed systems spontaneously protonated H2O and NH3 in the gas phase giving stable ion pair clusters.